Trichomoniasis injury evil-looking pseudo - Perea, Jorge (2015)
One case was a young woman and symptoms that were diagnosed with unflattering future with some confirmation in complementary diagnosis was presumed, but thanks to the inestimable value of research led to the conclusion by more flattering.